Implementation of a Sweet Potato Washing Machine for Brayan Grubi SMEs in Salaman District, Magelang Regency - Rany Puspita Dewi; Trisma Jaya Saputra; Sigit Iswahyudi; Adityo Noor Setyo Hadi Dharmo; Herru Santosa Budiono; Bagus Yustia; Cahyo Sejati (Warta LPM, 2026)
Brayan Grubi, a small and medium enterprise (SME), located in Jetis, Menoreh Village, Salaman, Magelang Regency. It processes approximately 150 kg of sweet potatoes daily to make traditional food grubi. The grubi production process, from washing to packaging, is still done manually, known as "gejrug." This manual washing process is time-consuming, labor-intensive, and unhygienic. The purpose of this community partnership program is to design and manufacture a sweet potato washing machine so that the washing process of sweet potatoes as a raw material for making grubi becomes more efficient and hygienic. The process becomes more efficient because the washing process takes less time and is more hygienic because the washing process is carried out using the help of a machine. This activity is carried out in four stages. The first stage is data collection as a basis for machine design and is continued in coordination with partners. The second stage is the construction and testing of the sweet potato washing machine. The third stage is the implementation of the sweet potato washing machine. The last stage is evaluation of machine implementation by the team. The efficiency of the sweet potato washing process is measured by calculating the washing time of 150 kg of sweet potatoes. The implementation of the sweet potato washing machine increases the washing process efficiency from 20 minutes to 5 minutes per 15 kg of sweet potatoes. The interview results show that the activity increases partners' understanding from 20% to 100%, about the more hygienic washing process of the sweet potato washing machine.